Surgical treatment of acute calculous cholecystitis complicated with hepatic dysfunction. Issue 24 (12th June 2020) - Tian, Yuanhu; Suo, Xiaopeng
Abstract : Abstract: To evaluate the timing, feasibility, and necessity of early laparoscopic cholecystectomy (LC) in the management of patients with acute calculous cholecystitis complicated with hepatic dysfunction. The clinical data of 60 patients with acute calculous cholecystitis complicated with hepatic dysfunction treated from January 2016 to January 2018 were analyzed retrospectively. A total of 32 patients underwent LC within 72 hours of the cholecystitis attack, 28 patients after 72 hours. The results were compared with those from 28 patients with delayed LC. All the patients were operated by experienced surgeons, and no LC transfer to open operation. No significant differences were detected in the operation time, postoperative complications, intraoperative blood loss, white TBIL, ALT, GGT before and after the operation between the 2 groups ( P  > .05). Patients who underwent early LC had a short hospital stay and fewer hospital costs ( P  < .05). All the patients were cured. It is safe, feasible, and necessary to perform LC within 72 hours in patients with acute calculous cholecystitis complicated with hepatic dysfunction. Such patients show a high positive correlation between the inflammation of acute calculous cholecystitis and the damage of hepatic function.